ANALYSIS OF MECHANICAL PROPERTIES OF CARBON FIBER REINFORCED POLYMER (CFRP) COMPOSITE MATERIALS USING MULTISCALE MODELING METHOD - Iqbal Alfarizi, M.
Carbon fiber reinforced polymer (CFRP) composite material is widely used in various fields because of its advantages such as light weight, strength, and corrosion resistance. Knowledge of the mechanical properties of materials such as elastic properties is very important to optimize the advantages of CFRP. The elastic properties of CFRP can be obtained by various approaches, one of which is numerical simulation of finite element with multiscale modeling. In this final project, numerical simulations will be carried out starting from the micro scale, meso scale to macro scale. Micro-scale modeling was carried out on unit cells with several variations such as the type of unit cell packing and fiber volume fraction. At the meso scale, the elastic properties of the unit cell are obtained and at the macro scale, periodic boundary conditions and variations in interphase properties are applied to observe the mechanical behavior. Fiber strength plays an important role in the strength of the CFRP structure which is illustrated by the greater the volume fraction value of the fiber, the greater the strength value of the composite structure. It was found that the maximum strength of a CFRP structure during normal longitudinal loading was 5782.65 MPa. It was also found that the smaller the interphase stiffness, the larger the cohesive zone model damage parameter which initiates the occurrence of interfacial debonding and makes the modulus of elasticity of the CFRP structure also smaller. The modulus of elasticity of CFRP was found to be greatest at normal longitudinal loading of 115652.99 MPa by applying a fiber volume fraction of 0.342 and an interphase stiffness of 2 × 109 N/mm3.